Political control over executive departments in India - Maheshwari, Shriram (1980)
The power of the executive branch of the government which handles varied functions must always be balanced with those of the legislature and the judiciary. In India, this balancing control has to comply with the fundamental features of its Constitution. Being under a parliamentary form of government in itself provides two forms of control over the executive: a control which holds the political executive accountable to the legislature and a control in the form of a political executive which is actually the council of ministers with the Prime Minister at its head. In addition, control is also exercised by the political parties, mass media, pressure groups, etc. These old mechanisms, however, have proven to be insufficient: the Parliament cannot sustain effective control over the executive; control by the press suffers from outside influences, and control by pressure groups although occasionally has fruitful results will entail harmful consequences if done on a large scale. Thus, the different control mechanisms need restructuring and redesigning to cope with the expanding power of the executive.
Keywords: Parliamentary system -- India; Parliamentary government; Politics and government -- India